Hospital-Acquired Versus Community-Acquired Acute Kidney Injury in Patients With Cirrhosis: A Prospective Study. (5th September 2020) - Patidar, Kavish R.; Shamseddeen, Hani; Xu, Chenjia; Ghabril, Marwan S.; Nephew, Lauren D.; Desai, Archita P.; Anderson, Melissa; El-Achkar, Tarek M.; Ginès, Pere; Chalasani, Naga P.; Orman, Eric S.
Abstract : INTRODUCTION: In patients with cirrhosis, differences between acute kidney injury (AKI) at the time of hospital admission (community-acquired) and AKI occurring during hospitalization (hospital-acquired) have not been explored. We aimed to compare patients with hospital-acquired AKI (H-AKI) and community-acquired AKI (C-AKI) in a large, prospective study. METHODS: Hospitalized patients with cirrhosis were enrolled (N = 519) and were followed for 90 days after discharge for mortality. The primary outcome was mortality within 90 days; secondary outcomes were the development of de novo chronic kidney disease (CKD)/progression of CKD after 90 days. Cox proportional hazards and logistic regressions were used to determine the independent association of either AKI for primary and secondary outcomes, respectively. RESULTS: H-AKI occurred in 10%, and C-AKI occurred in 25%. In multivariable Cox models adjusting for significant confounders, only patients with C-AKI had a higher risk for mortality adjusting for model for end-stage liver disease-Na: (hazard ratio 1.64, 95% confidence interval [CI] 1.04–2.57, P = 0.033) and adjusting for acute on chronic liver failure: (hazard ratio 2.44, 95% CI 1.63–3.65, P < 0.001). In univariable analysis, community-acquired-AKI, but not hospital-acquired-AKI, was associated with de novo CKD/progression of CKD (odds ratio 2.13, 95% CI 1.09–4.14, P = 0.027), but in multivariable analysis, C-AKI was not independently associated with de novo CKD/progression of CKD. However, when AKI was dichotomized by stage, C-AKI stage 3 was independently associated with de novo CKD/progression of CKD (odds ratio 4.79, 95% CI 1.11–20.57, P = 0.035). DISCUSSION: Compared with H-AKI, C-AKI is associated with increased mortality and de novo CKD/progression of CKD in patients with cirrhosis. Patients with C-AKI may benefit from frequent monitoring after discharge to improve outcomes.